Immune cells within tertiary lymphoid structures are associated with progression‐free survival in patients with locoregional recurrent breast cancer - Jinyuan Gu; Jiaming Wang; Yue Sun; Xinrui Mao; Chao Qian; Xinyu Tang; Ji Wang; Hui Xie; Lijun Ling; Yi Zhao; Xiaoan Liu; Kai Zhang; et al. (Cancer Medicine, 2024)
Abstract Introduction Locoregional recurrent breast cancers have a poor prognosis. Little is known about the prognostic impact of immune microenvironment, and tertiary lymphoid structures (TLSs) in particular have not been reported. Thus, we aimed to characterize the immune microenvironment in locoregional recurrent breast tumors and to investigate its relationship with prognosis. Methods We retrospectively included 112 patients with locoregional recurrent breast cancer, and hematoxylin–eosin staining and immunohistochemical staining (CD3, CD4, CD8, CD19, CD38, and CD68) were performed on locoregional recurrent tumor samples. The association of immune cells and TLSs with progression‐free survival (PFS) were analyzed by survival analysis. Results We found more immune cells in the peritumor than stroma. After grouping according to estrogen receptor (ER) status, a low level of peritumoral CD3+ cells in ER+ subgroup (p = 0.015) and a low level of stromal CD68+ cells in ER− subgroup (p = 0.047) were both associated with longer PFS. TLSs were present in 68% of recurrent tumors, and CD68+ cells within TLSs were significantly associated with PFS as an independent prognostic factor (p = 0.035). TLSs and immune cells (CD3, CD38, and CD68) within TLSs were associated with longer PFS in ER− recurrent tumors (p = 0.044, p = 0.012, p = 0.050, p < 0.001, respectively), whereas CD38+ cells within TLSs were associated with shorter PFS in ER+ recurrent tumors (p = 0.037). Conclusion Our study proposes potential predictors for the clinical prognosis of patients with locoregional recurrent breast cancer, emphasizing the prognostic value of immune cells within TLSs, especially CD68+ cells.